DEVELOPMENT OF LEARNING MANAGEMENT SYSTEM IN VOCATIONAL SCHOOL OF YAMACO NEGERI KATON BASED ON ENTERPRISE ARCHITECTURE PLANNING AND COMPUTER SUPPORTED COLLABORATIVE LEARNING - Idris, Muhammad (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2020)
The development of information systems and technology requires planning to complement the direction of high the development of information systems to complement the strategic direction and management of high schools and above to manage effective and efficient teaching and learning process needs to adopt the concept of electronic learning. In managing electronic learning, a Learning Management System is needed that is able to manage learning content that is more updated and makes learning easier. This Learning Management System (LMS) uses a Computer-Supported Collaborative Learning approach. The design of this LMS uses the Enterprise Architecture Planning (EAP) method as a strategic planning approach to defining data architecture, applications, and technology in the use of information to support business processes then architectural design to identify needs and create architectural schemes and make plans to implement them. The use of computer-supported collaborative learning (CSCL) is a learning model that brings the benefits of collaborative and cooperative learning models for learner actors that are localized with a computer network. The concept of CSLS learning does provide a different perspective on the teaching and learning process. The system design uses the RUP methodology. The methodology has four phases, namely Inception, Elaboration, Construction, and Transition. However, not all phases were carried out in this research. Only two phases were carried out in this study, namely Inception and Elaboration